Performance analysis of digital modulation, bit dilation and signal level through AWGN channel - Kumar, Rajesh; Prasad, Ganga; Tiwari, Neha; Tripathi, Sneha; Yadav, Ram Chandra (My University, 2014)
In this paper performance of digital modulations like FSK, BPSK and QPSK using CRC coded data are analyzed. These digital modulations are widely used in data transfer in mobile phone, scientific and geomagnetic instruments etc. The performance of these modulations is compared with each other. The simulation is carried out through AWGN Channel and obtains the bit error rate by varying the signal to noise ratio of the AWGN channel. The performance of these modulations is evaluated by calculating the bit error rate versus signal to noise ratio. We have also compared bit delay at receiving end with sending end of bit timing. Spectrum power levels are also measured at transmitting and receiving end. This paper may be useful for further analysis and computation of theoretical and practical result.
Keywords: Frame check sequence; Frequency-shift keying; Bi-polar phase shift keying; Quadrature phase shift keying